Implementation of Biological Education Based on Local Wisdom of Dairy Cattle Breaking in the Pasuruan Puspo Area: Pelaksanaan Pendidikan Biologi Berbasis Kearifan Lokal Pemecah Sapi Perah di Kawasan Puspo Pasuruan - pipit novita Krisna Putri; Endang Sulistyawati Ningsih; Lailatul Maghfiroh; Uthurul Jannah (Tinta Emas Publisher, 2023)
Based on local wisdom, they held a biology class for Puspo's dairy cowsespecially for membership products based on local wisdom. This KUD is an effort to present the competitiveness of the Puspo community in the midst of changing times. From the results of interviews (documents), it appears that KUD self-help depends on the conditions of the era of intense competition, therefore not many residents do not have more modern information. This observation shows that ITSNU PASURUAN students and Puspo Vocational School students have succeeded in collaborating with KUD Sembada Puspo. This is in accordance with the concept of educational innovation which incorporates local wisdom values. especially for membership products based on local wisdom. This KUD is an effort to present the competitiveness of the Puspo community in an era that continues to develop. Puspo's local culture is preserved there. Puspo's local culture is preserved there. In addition, KUD is a cooperative that manages “Sembada Puspo” cattle. For this feed, a 1400 kg cow should eat 7.5 kg per day or 1.5 bags in 10 days.